A framework to understand gender and structural vulnerability to climate change in the Ganges River Basin: lessons from Bangladesh, India and Nepal - Sugden, Fraser; de Silva, Sanjiv; Clement, Floriane; Maskey-Amatya, Niki; Ramesh, Vidya; Philip, Anil; Bharati, Luna (International Water Management Institute, 2014)
As climate change becomes accepted as a reality in the scientific community, it is critical to continue to understand its impact on the ground, particularly for communities dependent on agriculture and natural resources. This report reviews the extensive literature on the vulnerability to climate change in South Asia, with a focus on gender. It highlights how vulnerability is intricately connected to existing social structures. With respects to gender inequalities, the report reviews how men and women are affected in different ways by climate shocks, while differing access to resources and cultural ideologies mean that their capacity to ‘adapt’ is also not equal. The report also notes the importance of other axes of inequality (caste, class and ethnicity) in shaping gendered vulnerability. It concludes by offering insights into potential ways forward to promote more equitable adaptation to change through improved policies and practices.